2020
DOI: 10.1007/s11881-020-00196-9
|View full text |Cite
|
Sign up to set email alerts
|

Latent profile analysis of students’ reading development and the relation of cognitive variables to reading profiles

Abstract: Previous studies have showed that early problems with word decoding can lead to poor performance in text reading and comprehension and suggest that poor readers often struggle with reading deficits throughout their school years. Therefore, early detection of those children who are at risk for slow reading development and/or who belong to the lowest reading profiles is essential in order to organize proper support. The present study explores the heterogeneity and prevalence of latent reading profiles among 769 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…In fact, the majority of studies with English-speaking children have identified five profiles in preschoolers (Cabell et al, 2011), in children from kindergarten to Grade 2 (Boscardin et al, 2008) and in Grade 1 (Foorman et al, 2017;Grimm et al, 2018). However, only four profiles have been identified in other languages, namely in Dutch with children in kindergarten (Verwimp et al, 2020) and in German and Finnish in Grade 1 and Grade 2 children (Holopainen et al, 2020). We have no hypothesis about this small difference (4 or 5 profiles) and how the type of language might influence the number of profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the majority of studies with English-speaking children have identified five profiles in preschoolers (Cabell et al, 2011), in children from kindergarten to Grade 2 (Boscardin et al, 2008) and in Grade 1 (Foorman et al, 2017;Grimm et al, 2018). However, only four profiles have been identified in other languages, namely in Dutch with children in kindergarten (Verwimp et al, 2020) and in German and Finnish in Grade 1 and Grade 2 children (Holopainen et al, 2020). We have no hypothesis about this small difference (4 or 5 profiles) and how the type of language might influence the number of profiles.…”
Section: Discussionmentioning
confidence: 99%
“…After a latent profile analysis on scores in PA, RAN, LNK, and IQ, they obtained four profiles, with the two profiles with the lowest scores being distinguished by IQ, having either average (25.6%) or belowaverage IQ (17.7%). In a longitudinal study (Holopainen et al, 2020), 445 German-speaking children and 324 Finnish children performed several reading tasks in two sessions, one in G1 and the other in G2. Classical tasks were used to investigate PA, LSK, WR, fluency and reading comprehension (at sentence level).…”
Section: Examining Heterogeneity In Literacy Skillsmentioning
confidence: 99%
“…As a second step, this study employed the logistic regression to examine the relation of cognitive-linguistic variables (i.e., phonological awareness, phonological memory, rapid automatized naming, vocabulary, listening comprehension, sentence repetition, and nonverbal ability) to reading achievement profiles. The logistic regression was used to predict the categorical dependent variables based on one or more independent variables (Holopainen et al, 2020). In this study, the subgroups identified through the latent profile analysis was used as dependent variables and cognitive-linguistic variables were used as independent variables.…”
Section: Methodsmentioning
confidence: 99%
“…Several researchers advocate the creation of learners' reading profiles in an effort to address learners' reading difficulties in many countries around the world (Caner, Vural & Yalcin 2021;Dinsmore et al 2019;Holopainen, Hoang & Kofler 2020;Karlsson et al 2018;Mouzaki & Sideridis 2007). South Africa is no exception.…”
Section: Introductionmentioning
confidence: 99%
“…Pokharel further refers to the reading strategies such as predicting, connecting, comparing, inferring, synthesising, re-reading, et cetera. Previous studies have shown that profiling learners' reading strategies is critical for the timely identification of those learners who are at risk, allowing for the effective organisation of support (Holopainen et al 2020). At-risk learners are individuals or groups who are thought of as those who are more likely to perform poorly academically or drop out.…”
Section: Introductionmentioning
confidence: 99%